2012
DOI: 10.3748/wjg.v18.i9.938
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal stenting for malignant gastric outlet obstruction: Prospective study

Abstract: Enteral stenting to alleviate gastroduodenal malignant obstruction improves quality of life in patients with limited life expectancy, which can be evaluated by using a GOO scoring system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 26 publications
2
13
0
4
Order By: Relevance
“…This is the fourth report on the use of an enteral WallFlex stent only. In previous studies, complications relevant to enteral WallFlex stent placement, namely hemorrhage (0–4%), perforation (0–5%), cholangitis (2–6%), and sepsis (0–2%) have been reported (Table ) . Post‐procedural pancreatitis has never been reported with the use of a WallFlex stent.…”
Section: Discussionmentioning
confidence: 99%
“…This is the fourth report on the use of an enteral WallFlex stent only. In previous studies, complications relevant to enteral WallFlex stent placement, namely hemorrhage (0–4%), perforation (0–5%), cholangitis (2–6%), and sepsis (0–2%) have been reported (Table ) . Post‐procedural pancreatitis has never been reported with the use of a WallFlex stent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported perforation, bleeding, abdominal pain, obstruction and migration of the SEMS 13 32 33 34 35. High heterogeneity was observed in the overall complications analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Rövidítések ERCP = endoszkópos retrográd cholangiopancreatographia; Fr = French, mértékegység, 1 French = 0,33 mm; GOOSSscore = (Gastric Outlet Obstruction Scoring System) a gyomorkimenet-elzáródás mértékét meghatározó skála; in = inch, mértékegység, 1 inch = 2,54 cm; PTD = percutan transhepaticus drenázs A malignus gastroduodenalis obstrukció hátterében leggyakrabban a pancreatobiliaris rendszer -elsősorban a pancreasfej -daganatos elváltozásai, illetve peripyloricus gyomortumorok, valamint a duodenum elsődleges vagy másodlagos daganatos elváltozásai állnak [1,2,3]. A klasszikus sebészeti palliáció -gastroenteroanastomosis -mellett vagy helyett hazánkban is egyre több endoszkópos centrumban válik gyakorlattá az enteralis stenttel történő endoszkópos palliáció [3,4,5].…”
Section: Eredeti Közleményunclassified
“…A klasszikus sebészeti palliáció -gastroenteroanastomosis -mellett vagy helyett hazánkban is egyre több endoszkópos centrumban válik gyakorlattá az enteralis stenttel történő endoszkópos palliáció [3,4,5]. [1,6,7]: -öntágulós fedetlen fémstent, -fedett fémstent [8], -részlegesen fedett, úgynevezett "big cup" Hanaro DPC-stent [9], -60-80-100-120-140 mm hossz-és 18-20-22-24 mm átmérőméretek.…”
Section: Eredeti Közleményunclassified
See 1 more Smart Citation